2017
DOI: 10.1111/jam.13619
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of O -methyltransferases used to catalyse site-specific methylation in the post-tailoring steps of pradimicin biosynthesis

Abstract: Aims: To identify the roles of the two O-methyltransferase homologous genes pdmF and pdmT in the pradimicin biosynthetic gene cluster of Actinomadura hibisca P157-2. Methods and Results: Pradimicins are pentangular polyphenol antibiotics synthesized by bacterial type II polyketide synthases (PKSs) and tailoring enzymes. Pradimicins are naturally derivatized by combinatorial O-methylation at two positions (i.e., 7-OH and 11-OH) of the benzo[a]naphthacenequinone structure. PdmF and PdmT null mutants (PFKO and PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…More recently, Wang et al (2019) have studied the use of two fungal MTs to produce unnatural O-methylated benzenediol lactone polyketides. Other studies have shown that O-methyltransferases can be used to obtain new compounds by modifying the glycosyl moieties of polyketides ( Patallo et al, 2001 ; Han et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Wang et al (2019) have studied the use of two fungal MTs to produce unnatural O-methylated benzenediol lactone polyketides. Other studies have shown that O-methyltransferases can be used to obtain new compounds by modifying the glycosyl moieties of polyketides ( Patallo et al, 2001 ; Han et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PdmT was identied as a 7-O-methyltransferase, which is subsequently followed by a yet to be characterized process involving C-7 demethoxylation and C-14 hydroxylation. 118,119 The glycosyltransferase PdmS is responsible for attachment of the rst sugar, 4 ′ ,6 ′ -dideoxy-4 ′ -amino-D-galactose, at the 5-OH, followed by attachment of D-xylose to the 3 ′ -OH of the rst sugar, catalysed by PdmQ. 120,121 The N-methyltransferase PdmO has been suggested to methylate the 4 ′ -NH 2 of the 4 ′ ,6 ′ -dideoxy-4 ′ -amino-D-galactose moiety.…”
Section: Pradimicinsmentioning
confidence: 99%
“…The compound specically exhibited good activity against dermatophytic fungi. 127,128 2.8 Anthracyclines Akrobomycin (116), 129 carminomycins I (117), 130,131 II (also known as rubeomycin A and 4-hydroxybaumycin A 2 ) (118), and III (also known as rubeomycin A 1 and 4-hydroxybaumycin A1) (119), [132][133][134][135] barminomycins I (120) and II (121), 136,137 and rubeomycins B (122) and B 1 (123), 133,135 are all produced by Actinomadura and are extremely potent cytotoxic agents (Fig. 14).…”
Section: Anthronesmentioning
confidence: 99%
“…Different tailoring processes can be observed, but according to the modifying enzymes, they can be classified into two general categories. Online tailoring enzymes are trans ‐acting enzymes that engage with the multi‐enzymatic PKS/NRPS complex and perform modifications during the core intermediate synthesis, like β‐branching enzymes in trans ‐AT PKSs (Calderone, 2008 ) or amino acid heterocyclizations in NRPSs (Sundaram & Hertweck, 2016 ), while the other tailoring enzymes allow the post‐PKS modifications such as hydroxylations and methylations (Han et al, 2018 ; Mohammad et al, 2018 ). The pederin family of polyketides is a group of compounds, including mycalamides A and B, theopederins, psymberin and diaphorin besides pederin and labrenzin that share much of their core structure with that of pederin but contain different tailoring modifications (Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%